2021
DOI: 10.1002/rse2.221
|View full text |Cite
|
Sign up to set email alerts
|

Interpolating missing land cover data using stochastic spatial random forests for improved change detection

Abstract: Forest cover requires large scale and frequent monitoring as an indicator of biodiversity and progress towards United Nations and World Bank Sustainable Development Goal 15. Measuring change in forest cover over time is an essential task in order to track and preserve quality habitats for species around the world. Due to the prohibitive expense and impracticality of mass field data collection to monitor forest cover at regular intervals, satellite images are a key data source for monitoring forest cover global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This strategy was used to produce the first land use and land cover maps in France [12] and is now commonly used at large scale. Yet, for other applications, e.g., changes detection, the interpolation algorithm choice may be more critical than for pixel-wise classification [72].…”
Section: Classification Resultsmentioning
confidence: 99%
“…This strategy was used to produce the first land use and land cover maps in France [12] and is now commonly used at large scale. Yet, for other applications, e.g., changes detection, the interpolation algorithm choice may be more critical than for pixel-wise classification [72].…”
Section: Classification Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to use pixel-based classification to extract Pedicularis, and feature engineering is a particularly useful method. Some work in the literature has indicated that spectral features and combined vegetation indices are more essential than textural features and principal components in target identification and classification [41,42].…”
Section: Planetscope Imagerymentioning
confidence: 99%
“…Random forests can identify and rank the variables of importance for making predictions (Tyralis et al 2019), which can aid ecologists in recognizing which measured variables to retain in long‐term monitoring, recognize if unmeasured (latent) variables exist and caused low prediction accuracy, and determine ecological relationships. Another neat application can use random forest prediction errors in space–time, such as particular aquatic habitats or periods in time, which may reveal habitat heterogeneity, spatiotemporal variability and dynamics (Chiao et al 2012; Louvet et al 2016; Vizcaino et al 2016) and detect change under a range of simulated scenarios (Holloway‐Brown et al 2021). Random forest outputs can also link conceptually to places with high ecological resiliency or risk of ecological state transitions that could inform aquatic management and restoration priorities (Delaney and Larson, in review).…”
Section: Assessmentmentioning
confidence: 99%